Flexible CsPbCl3 inorganic perovskite thin-film detectors for real-time monitoring in protontherapy - Bruzzi, M.; Calisi, N.; Enea, N.; Verroi, E.; Vinattieri, A. (Frontiers in Physics, 2023)
Lead halide inorganic perovskite, CsPbCl3, 0.4-1um-thick films have been grown for the first time on plastic flexible substrates equipped with interdigitated electrodes (IDEs) by magnetron sputtering at room temperature. First measurements in real-time configuration are reported for a 1-m thick prototype under proton beams with energy in the range 100-228MeV and 1-10nA extraction currents, of interest for protontherapy applications. Experimental results evidence good performances of our sample as a real-time monitoring device. Current stability under UV and proton beam exposure has been tested in the range 0.1-120s, as well as reproducibility under multiple exposures. The measured current signal proved to be linearly dependent on the extraction currents at a given proton energy. Linearity of the current signal of the device with proton fluxes was also proved within two order of magnitude range, about 10^7 – 10^9 p/s. These promising results, when coupled with easyness of fabrication, low processing costs and high versatility of electrode configurations, all features characterizing the manufacturing process, put into evidence lead halide perovskites as promising candidates for real-time radiation detection in protontherapy.